Возрастные изменения уровня физической подготовленности юных футболистов 8-12 летразличных соматических типов - Григорян, М. С.
Parameter and correlation analysis revealed the presence of a close relationship with the overall performance level coordination of preparedness and the condition of their manifest ation in the gaming activities, which is e© ecially important to consider for their development. Longitudinal observation during the completely playing season the level of motor readiness players 8-12 years of various somatic types and variants of physical development demonst rated the need to incorporate indicators of dimensional variation with increasing and assessing the level of physical fi tness. It must be assumed that in this age of somatic type, the est imated level of the dimensional variation should be the criterion of individualization of physical training.
Keywords: Физическое развитие